Pengaruh Social Media Marketing Dan Electronic word of mouth Terhadap Purchase decision Melalui Brand Awareness Pada Produk Kopi Kenangan - Rahayu, Cantika Putri; Witjaksono, Beny (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
This research is a quantitative study with a causal relationship to determine the direct effect of Social Media Marketing, Electronic word of mouth on Brand Awareness, and Purchase Decision through Brand Awareness of Kenangan Coffee products. The population in this study are those who already know Kopi Kenangan products, have bought Kopi Kenangan, live in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), and are at least 17 years old. The questionnaire collected 183 respondents using the linkert scale formula 1-5. The sampling method used is non-probability sampling with purpose sampling technique to test validity and reliability using SmartPLS software. Based on the research results, of the 7 accepted hypotheses, namely Social Media Marketing has a positive effect on brand awareness, electronic word of mouth has an effect on brand awareness, social media marketing and electronic word of mouth do not affect purchase decisions, social media marketing has an effect on purchase decision, e-service through brand awareness and electronic word of mouth has no effect on purchase decision through brand awareness.